Ce que la littérature fait au droit : le cas Emmanuel Carrère - Nicolas Thirion (Contextes)
In D’autres vies que la mienne, Emmanuel Carrère carefully describes the fight of some French judges against the abuses of credit companies against their over-indebted clients. In this a priori repulsive context, Carrère manages to deconstruct the myths, which form the fundament of legal science, of axiological universality and neutrality of law and jurists. Carrère’s book thus reveals what legal dogmatism seeks to mask : the preponderant place that judges occupy in the construction and evolution of law and power relations which characterize the legal field. In doing so, Carrère’s non-fiction allows us to show the preponderance of fiction contained in the law, which is a condition sine qua non of the acceptability, and therefore of the efficiency, of the violence that the agents of legal systems are able to exercise.